Influência da amamentação e do contato mãe-filho na primeira hora de vida sobre os índices de aleitamento materno - Marques, Cristina Elias (2012)
Scientific evidence proves that breastfeeding is a strategy for reducing child mortality and also a strategy for promoting the physical, mental and psychic health of the child and breastfeeding woman. This study aimed at evaluating the influence of time as to beginning of first breastfeed and early mother-infant contact in establishing and maintaining breastfeeding. This was a prospective cohort study conducted in a public university hospital which is a regional reference in Minas Gerais. The study population consisted of 812 mothers/newborn babies. Two questionnaires and a card for data collection were used. The time of beginning of first breastfeeding and early motherinfant contact and the presence of breastfeeding in 1st, 3rd and 6th month of the child s life were analyzed. Bivariate analysis and multiple linear regressions were performed. Of the 812 mother-child binomials, 329 (40.5%) breastfed in the first hour of life and 529 (65.1%) made contact with the mother in the delivery room. The bivariate and multivariate analyzes showed that the early initiation of breastfeeding and contact between mother and child are directly related to the maintenance of breastfeeding and only mother s milk in the 1st, 3rd and 6th month of the child\'s life. It was concluded that both breastfeeding in the first hour of life and the practice of early mother-child contact positively influenced the establishment and maintenance of breastfeeding. The information from this study contributes to the development of public health recommendations that encourage early initiation of mother-child interaction.